Impact of Urbanization on the Tribal Population of Jharkhand - Minz, Stuti Priya; Moirangleima, Kh. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The current paper tries to study the impact of urbanization of local tribal people in Jharkhand. Since the majority population from rural areas are inclined towards urban areas due to availability of more opportunities of earning, resulting positive impact in their lifestyle. It further able to provide better education to their children and several other things. In this the tribal population of Jharkhand who were also migrating towards urban areas at a very rapid pace for better life, earning more money, better education to children, but the negative impact of this results in uprooting not only from their land, village etc., but also resulted in changing their culture and language. The objective of this research is to find out the impacts of such tribal population migrating to big cities, whether it is really beneficial for them. As it was found that this development affects by taking them away from their inherent culture which is considered as their true identity. Data Base: This research is based on the analyzation of primary as well as secondary data collected from various sources and survey done in order to get the required information. Findings: Work concludes in finding the urbanization impact on tribal population in Jharkhand who migrate in search of better life and to earn more money so that they can fulfil their desires, and are they actually fulfilling their wishes by getting lost from their own culture.